The Significance of Using the Media in the Formation of Knowledge about Nature in Preschool Children - Luiza Turdikulova Zainiddinovna; Rakhimova Surayyo (International Journal on Orange Technologies, 2023)
As you know, preschool educational institutions are the main base of continuous education. In the years of independence, as a result of paying special attention to the training of qualified educators and teachers, its effectiveness has increased. This article discusses the ways and means of using the media in the formation of natural history knowledge in young children.